Pengaruh Informasi Kemanfaatan Penggunaan Obat Tradisional dan Suplemen Terhadap Willingness to Pay Dalam Pencegahan NCDs di Kota Yogyakarta - Arisa Mardiani; Eliza Dwinta; Raden Jaka Sarwadhamana; Imram Radne Rimba Putri (Universitas Wahid Hasyim Semarang, 2024)
The current incidence of NCDs can not only attack the elderly but can start at a younger age. Must carry out prevention efforts as early as possible by consuming traditional medicines (OT) and supplements. Can obtain information on the benefits of the two products through packaging labels. However, many people still need to pay more attention to them, so they need to understand the proper and correct use of OT and supplements. Willingness to pay (WTP) goes hand in hand with the benefit information obtained. Because if it follows the benefits and prices, the community's WTP is expected to increase. This study aimed to determine the effect of information on the benefits of using OT and supplements on WTP in preventing NCDs in Yogyakarta with a cross-sectional study design. They conducted this research for one month in 5 sub-districts of Yogyakarta City, namely Danurejan, Gondomanan, Mantrijeron, Umbulharjo, and Wirobrajan sub-districts with 107 respondents. The sampling technique uses accidental sampling, and the research instrument is a WTP questionnaire. The results of the research on statistical tests using Kendall Tau found that the significance values were 0.225 (OT) and 0.094 (supplements) > 0.05, so it concluded that information on the benefits of using OT and supplements from packaging labels did not affect WTP in preventing NCDs in the City of Yogyakarta.